1988
DOI: 10.1159/000185116
|View full text |Cite
|
Sign up to set email alerts
|

Paracetamol: A Cause for Analgesic Nephropathy and End-Stage Renal Disease

Abstract: 180 patients with end-stage renal disease (ESRD) on maintenance dialysis and those who had undergone renal transplantation were questioned retrospectively. 14 patients had consumed excessive quantities of analgesics ( > l kg) prior to the institution of long-term dialysis or transplantation. Sonographic examination done on these patients indicated that 7 had renal papillary necrosis (RPN). The sonographic features were renal papillary calcifications surrounding the central sinus in a complete or incomplete gar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…As with other non-steroidal anti-inflammatory drugs, paracetamol may cause acute renal failure following overdosage (Prescott, 1983), and there has been a single report of reversible acute tubular necrosis attributed to the use of therapeutic doses (Gabriel et al, 1982). There have been very few reports of analgesic nephropathy associated with paracetamol alone (Prescott, 1982;Segasothy et al, 1988) and its cumulative consumption during chronic use in patients with arthritis was not related to impairment of renal function (Edwards et al, 1971). The results of recent epidemiological studies have been conflicting.…”
Section: Urine Volume and Osmolalitymentioning
confidence: 99%
“…As with other non-steroidal anti-inflammatory drugs, paracetamol may cause acute renal failure following overdosage (Prescott, 1983), and there has been a single report of reversible acute tubular necrosis attributed to the use of therapeutic doses (Gabriel et al, 1982). There have been very few reports of analgesic nephropathy associated with paracetamol alone (Prescott, 1982;Segasothy et al, 1988) and its cumulative consumption during chronic use in patients with arthritis was not related to impairment of renal function (Edwards et al, 1971). The results of recent epidemiological studies have been conflicting.…”
Section: Urine Volume and Osmolalitymentioning
confidence: 99%
“…Paracetamol (acetaminophen), as the major me tabolite of phenacetin, has long been under suspicion [re viewed in ref. 6], but investigations of this relationship are rare and limited in numbers of patients included [7][8][9]. Long-term consumption of salicylates, even in pa tients with preexisting renal diseases, has not been demonstrated to promote renal dysfunction [10,11], Discussion regarding the relationship between RAI and AAN was stimulated once more by the results of a case-control study performed by Murray et al [12], In a population which was obviously low in RAI, no in creased RR of EF, whether for phenacetin or any analgesic combination, could be shown.…”
mentioning
confidence: 99%
“…About one-third of the 44 patients studied by the authors reported preceding chronic abuse of phenacetin-containing pain medications. Similar changes were also found after excessive long-term use of other analgesics containing phenacetin or acetaminophen as active ingredients whereas occasional reports data on aspirin-related nephrotoxicity were less convincing and in most cases negative [282][283][284][285][286]. Similar changes were also found after excessive long-term use of other analgesics containing phenacetin or acetaminophen as active ingredients whereas occasional reports data on aspirin-related nephrotoxicity were less convincing and in most cases negative [282][283][284][285][286].…”
Section: Analgesic Nephropathymentioning
confidence: 73%